Thermo‐erosional valleys in Siberian ice‐rich permafrost - Morgenstern, Anne; Overduin, Pier Paul; Günther, Frank; Stettner, Samuel; Ramage, Justine; Schirrmeister, Lutz; Grigoriev, Mikhail N.; Grosse, Guido; 1 Department of Permafrost Research Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Potsdam Germany; 6 Melnikov Permafrost Institute, Siberian Branch Russian Academy of Sciences Yakutsk Russia (Permafrost and Periglacial Processes, 2020)
Thermal erosion is a major mechanism of permafrost degradation, resulting in characteristic landforms. We inventory thermo‐erosional valleys in ice‐rich coastal lowlands adjacent to the Siberian Laptev Sea based on remote sensing, Geographic Information System (GIS), and field investigations for a first regional assessment of their spatial distribution and characteristics. Three study areas with similar geological (Yedoma Ice Complex) but diverse geomorphological conditions vary in valley areal extent, incision depth, and branching geometry. The most extensive valley networks are incised deeply (up to 35 m) into the broad inclined lowland around Mamontov Klyk. The flat, low‐lying plain forming the Buor Khaya Peninsula is more degraded by thermokarst and characterized by long valleys of lower depth with short tributaries. Small, isolated Yedoma Ice Complex remnants in the Lena River Delta predominantly exhibit shorter but deep valleys. Based on these hydrographical network and topography assessments, we discuss geomorphological and hydrological connections to erosion processes. Relative catchment size along with regional slope interact with other Holocene relief‐forming processes such as thermokarst and neotectonics. Our findings suggest that thermo‐erosional valleys are prominent, hitherto overlooked permafrost degradation landforms that add to impacts on biogeochemical cycling, sediment transport, and hydrology in the degrading Siberian Yedoma Ice Complex. Christiane Nüsslein‐Volhard Foundation European Research Council http://dx.doi.org/10.13039/501100000781 German Academic Exchange Service DAAD P.R.I.M.E. Helmholtz‐Gemeinschaft http://dx.doi.org/10.13039/501100001656 Polar Geospatial Center, NSF‐OPP awards RapidEye Science Archive (RESA) Russian Foundation for Basic Research http://dx.doi.org/10.13039/501100002261 Studienstiftung des Deutschen Volkes http://dx.doi.org/10.13039/501100004350 Universität Potsdam http://dx.doi.org/10.13039/501100004238 BMBF KoPf